Quadratura delle superficie e questioni connesse lectures given at the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Varenna (Como), Italy, August 16-25, 1954 - Bompiani, Enrico; C.I.M.E. Summer School Varenna, Italy, and Como, Italy (Berlin New York Springer Firenze C.I.M.E. Foundation, 2011)
L.Cesari: Appunti sulla teoria delle superficie continue.- C.Y. Pauc: Dérivés et intégrants. Fonctions de cellul
"Reprint of the 1st ed. C.I.M.E., Florence, 1954 ; with kind permission of C.I.M.E."
Electronic reproduction.
Keywords: Surfaces -- Congresses; Cell differentiation -- Congresses